2000
DOI: 10.1063/1.372047
|View full text |Cite
|
Sign up to set email alerts
|

Slip-free processing of 300 mm silicon batch wafers

Abstract: Articles you may be interested inTheoretical calculation of the acoustic force on a patterned silicon wafer during megasonic cleaning Under gravitational and thermal constraints of integrated-circuit ͑IC͒ process technology, 300-mm-diam silicon wafers can deform via slip dislocation generation and propagation, degrading the electrical characteristics of the leading edge device. We present a force balance model to describe the strain relaxation in large wafer diameter, which includes heat transfer effects and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Известны и другие способы крепления пластин: использование четырех симметрично расположенных опор и раз-мещение пластин на кольцевых опорах. В работе [7] в одномерном приближении проведены оценки максимальных сдвиговых напряжений в пластинах кремния диаметром 200 и 300 мм, обусловленных действием гравитационных сил, для перечисленных выше способов крепления пластин.…”
Section: моделирование напряженно− деформированного состояния и процеunclassified
“…Известны и другие способы крепления пластин: использование четырех симметрично расположенных опор и раз-мещение пластин на кольцевых опорах. В работе [7] в одномерном приближении проведены оценки максимальных сдвиговых напряжений в пластинах кремния диаметром 200 и 300 мм, обусловленных действием гравитационных сил, для перечисленных выше способов крепления пластин.…”
Section: моделирование напряженно− деформированного состояния и процеunclassified
“…The quality of oxide layer depends upon various factors like oxidation ambient, heating and cooling ramp rate etc. At temperatures higher than 750°C, the wafer becomes plastic in nature (Fischer et al, 2000). It has already been observed that the oxide charge generation in metal-oxide-semiconductor (MOS) devices significantly depend on the ramp up/down rate, experienced by the wafer (Ueno, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Under certain thermal treatments, slip can be introduced into silicon from the wafer's edge, and slip bands may extend across a significant fraction of the wafer. Slip bands have been observed by Fischer et al (2000), using Lang X-ray topography, to run in orthogonal h011i directions from near the edges of 300 mm wafers, and significant work has been done to model the stresses associated with the weight of these largediameter wafers (Bullis, 2000). There is some ambiguity in the literature as to whether the presence of slip has a major impact on device yield.…”
Section: Introductionmentioning
confidence: 99%